2003
DOI: 10.1016/s0006-3495(03)74853-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrophobic Surfactant Proteins SP-B and SP-C on Binary Phospholipid Monolayers

Abstract: In situ external reflection infrared spectroscopy at the air-water interface was used to study the influence on phospholipid structure of an endogenous mixture of the two hydrophobic surfactant proteins, SP-B and SP-C, which are thought to play pivotal roles in the adsorption and function of pulmonary surfactant. Mixtures studied were 1:1, 2:1, and 7:1 (mol:mol) DPPC-d(62):DPPG, and 7:1 DPPC-d(62):DOPG, alone and in the presence of 0.5-10 wt % mixed SP-B/C purified chromatographically from calf lung surfactant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 82 publications
(122 reference statements)
2
30
0
Order By: Relevance
“…4). The disposition of SP-B in lipid bilayers and monolayers as well as the effect produced on the lipids has been also analyzed by many different techniques such as 2 H NMR (Morrow et al, 1993(Morrow et al, , 2004, spin resonance (Perez-Gil et al, 1995), infrared spectroscopy (Brockman et al, 2003), atomic force microscopy (Cruz et al, 2004) or epifluorescence microscopy (Cruz et al, 2000).…”
Section: Sp-b: An Amphipathic Tag To the Interfacementioning
confidence: 99%
“…4). The disposition of SP-B in lipid bilayers and monolayers as well as the effect produced on the lipids has been also analyzed by many different techniques such as 2 H NMR (Morrow et al, 1993(Morrow et al, , 2004, spin resonance (Perez-Gil et al, 1995), infrared spectroscopy (Brockman et al, 2003), atomic force microscopy (Cruz et al, 2004) or epifluorescence microscopy (Cruz et al, 2000).…”
Section: Sp-b: An Amphipathic Tag To the Interfacementioning
confidence: 99%
“…The increment in uptake caused by SP-B at the high proteinto-lipid ratio could also be explained by changes in lipid conformation of the liposomes because SP-B is able to change lipid conformation of surfactant (5).…”
Section: Discussionmentioning
confidence: 99%
“…The first plateau observed is taken as evidence of removal of material from the monolayer. Previous studies propose that the material removed may be squeezed out into the subphase or form surface‐associated aggregates ( 18–21 ). Similar nonhorizontal plateaus are observed in many systems, and current theoretical investigations treat this behavior as arising from surface micelle formation ( 22,23 ).…”
Section: Discussionmentioning
confidence: 99%
“…SP‐C also exhibits the same partitioning. It has also been shown that SP‐B and SP‐C preferentially associate with anionic lipids ( 18,19 ). It then follows that the bright, expanded regions seen in the fluorescent images of the LS are also rich in anionic lipids.…”
Section: Discussionmentioning
confidence: 99%